HUBUNGAN RESILIENSI DIRI TERHADAP TINGKAT STRES PADA DOKTER MUDA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Tesa Willda; Elda Nazriati; Firdaus " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTResilience is the ability of individuals to adjust and adapt to change, the demands and disappointments that arise in life. Resilience can affect individuals in coping with stress, by Therefore, the individual must have resilience. The level of stress each indvidu influenced by an individual's ability to perform self-adjustment to the changes that occur. Good resilience can help a person in the face of stress. The purpose of this study was to determine the relationship between resilience ourselves on the level of stress on clerkship Riau University School of Medicine. Cross sectional analytic correlative design to 83 clerkship who selected by total sampling. Collecting data using questionnaire resilience based Connor- Davidson Resilience Scale (CD-RISC) and the Medical Student stressor Quisionaaire (MMSQ) using online questionnaire (goole docs). Data analyzed bivariat by Spearman correlation test and p value = 0.552, r = -0.066, meaning that there is no meaningful relationship with a weak correlation between the resilience of the level of stress on clerkship Riau University School of Medicine.Keywords: resiliensi, stress level, clinical clerkship